KESADARAN MEREK DAN PRESEPSI RISIKO DALAM MEMPENGARUHI NIAT BELI SEPATU "NIKE" - Azmi Farhan Fauzian; Driya Wiryawan; Dwi Asri Siti Ambarwati (Jurnal Riset Entrepreneurship, 2022)
Along with the times, sports shoes like “Nike” have now developed into more modern and fashionable shoes, so they can be used in daily activities. Brand awareness and risk perception influencing intention to buy “Nike” shoes is the aim of this research. Descriptive analytical research is the model chosen to conduct this research. 100 respondents were used as a sample in this study through purposive sampling and questionnaires as a way of collecting data. The result study shows that the age group of 17-25 years is the dominant age group using “Nike” products. This age group is a productive age group so they have a good understanding of “Nike” products. Multiple linear regression analysis of brand awareness affects significantly the purchase intention as its significant value is 0.237. This shows that most consumers of “Nike” shoes have good brand awareness. The risk perception variable in this study has a significant effect of 0.201 to the purchase intention. In theory, risk perception will have a negative impact on purchase intention. However, there is a positive direction of risk perception on purchase intention.